2018
DOI: 10.1186/s12970-018-0209-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional strategies of high level natural bodybuilders during competition preparation

Abstract: BackgroundCompetitive bodybuilders employ a combination of resistance training, cardiovascular exercise, calorie reduction, supplementation regimes and peaking strategies in order to lose fat mass and maintain fat free mass. Although recommendations exist for contest preparation, applied research is limited and data on the contest preparation regimes of bodybuilders are restricted to case studies or small cohorts. Moreover, the influence of different nutritional strategies on competitive outcome is unknown.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
113
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(135 citation statements)
references
References 51 publications
21
113
0
1
Order By: Relevance
“…In addition to resistance training, MP2, WW, and WB performed a high volume (>80 min) of aerobic exercise every day during the cutting phase, which is in agreement with the findings of previous studies [1][2][3][4]. However, a high volume and high frequency of concurrent aerobic training may increase catabolic state-led impairment of muscle gains [33].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition to resistance training, MP2, WW, and WB performed a high volume (>80 min) of aerobic exercise every day during the cutting phase, which is in agreement with the findings of previous studies [1][2][3][4]. However, a high volume and high frequency of concurrent aerobic training may increase catabolic state-led impairment of muscle gains [33].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, the participants reported using ephedrine, caffeine, clenbuterol, and synthetic thyroid hormones (T3 and T4) during the cutting phase. Considering that during the pre-contest phase there is an abrupt reduction in nutrients and caloric intake [2][3][4]21], the rationale for the use of stimulant-based substances during this phase is thought to be to avoid the reduced performance and increased perception of effort observed during severe caloric restriction [21,25]. However, the cost-benefit of this practice might be addressed critically, since the use of AAS might increase catecholamine release and β-adrenergic receptor expression [12], which might potentiate the harmful effects of stimulants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,9,10 Bodybuilders and fitness athletes (FA) are found to comply with these suggested "best methods". 3,[11][12][13] These athletes keep track of their total energy and macronutrient intake, eat fibrous foods, follow a high-protein diet, and diet for several weeks to allow for a slow rate of BW loss. 3,[11][12][13][14][15][16][17] The athletes also prepare meals for several days ahead, eat frequently during the day, and make sure to adjust meal intake according to the exercise sessions.…”
mentioning
confidence: 99%
“…3,[11][12][13] These athletes keep track of their total energy and macronutrient intake, eat fibrous foods, follow a high-protein diet, and diet for several weeks to allow for a slow rate of BW loss. 3,[11][12][13][14][15][16][17] The athletes also prepare meals for several days ahead, eat frequently during the day, and make sure to adjust meal intake according to the exercise sessions. [12][13][14][15] Additionally, they emphasize resistance exercise, [13][14][15][16][17] which specifically may be favorable in reducing the detrimental effect of dieting and low BW on lean body mass and BMD.…”
mentioning
confidence: 99%